Selective Hepatic Vascular Exclusion versus Pringle Maneuver in Major Hepatectomy: A Systematic Review and Meta-Analysis - Mobarak, Shahd; Stott, Martyn C.; Tarazi, Munir; Varley, Rebecca J.; Davé, Madhav S.; Baltatzis, Minas; Satyadas, Thomas (Frontiers in Surgery, 2022)
Objectives Mortality and morbidity following hepatic resection is significantly affected by major intra-operative blood loss. This systematic review and meta-analysis evaluates whether selective hepatic vascular exclusion (SHVE) compared to a Pringle manoeuvre in hepatic resection reduces rates of morbidity and mortality. Methods A systematic review and meta-analysis were conducted according to the PRISMA guidelines by screening EMBASE, MEDLINE/PubMed, CENTRAL and SCOPUS for comparative studies meeting the inclusion criteria. Pooled odds ratios or mean differences were calculated for outcomes using either fixed- or random-effects models. Results Six studies were identified: three randomised controlled trials and three observational studies reporting a total of 2,238 patients. Data synthesis showed significantly decreased rates of mortality, overall complications, blood loss, transfusion requirements, air embolism, liver failure and multi-organ failure in the SHVE group. Rates of hepatic vein rupture, post-operative haemorrhage, operative and warm ischaemia time, length of stay in hospital and intensive care unit remained the same. Conclusion Performing SHVE in major hepatectomy may result in reduced rates of morbidity and mortality when compared to a Pringle manoeuvre. The results of this meta-analysis are based on studies where tumours were adjacent to major vessels. Further RCTs are required to validate these results.